Analysis of the lost value of street trees in the context of the possibility of replacement and compensatory planting based on the case of selected streets in Warsaw - Suchocka, Marzena; Kosiba, Agnieszka; Milanowska, Agata (Ecological Questions, 2018)
Street trees grow in extreme habitat conditions and are exposed to high anthropogenic pressure. This study presents changes that occurred in the resources of street trees in the selected part of Praga-North, a district located near the center ofWarsaw, between 2011 and 2016. During this period, the number of dead and removed trees was determined and the assessment of the lost value was conducted. The compensatory value was evaluated as well. The replacement value was estimated in the examined area based on the difference between the value of the removed and newly-planted trees. The study also shows the real number of conducted compensatory planting for the environmental loss. The research was conducted with the objective to determine the changes in the urban forest in the selected, highly-urbanized part ofWarsaw. The study evaluated the extent of losses between the removed and newly-planted trees that allowed to assess the range of substitutes needed to be planted.